Gene Expression Evaluation of Intracellular Adhesins and Regulatory Genes among Biofilm Producing MRSA Isolates - Abdrabaa, Mariam Khamees; Abd Aburesha, Rasmiya (Iraqi Journal of Science, 2023)
The gene expression of the most important structural genes ica A and D of biofilm, sarA, and sigB regulatory genes of some methicillin-resistant Staphylococcus aureus (MRSA) isolates were examined using the real-time polymerase chain reaction after 24 hours of growth. The results revealed that the isolates with strong biofilm production had the highest gene expression of the structural icaA and D genes. Whereas the isolates that showed moderate and weak biofilm production, recorded the lowest gene expression. The results of the regulatory genes sarA, and sigB fluctuated among all MRSA isolates. Isolate No. 64 recorded the highest gene expression, while isolate 50 recorded the lowest gene expression. The purpose of this study was to determine the gene expression of structural genes ica A and D, and regulator genes sigB and sarA in some MRSA isolates with different abilities of biofilm formation where the sarA and sigB play important role in positive regulation of biofilm formation.